DAKWAH MELALUI PUJI-PUJIAN DI MUSHOLLA AL-UKHUWAH KOTA BARU DRIYOREJO GRESIK - MOHAMMAD ROFIQ (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2022)
Hymns of praise that are usually read by worshipers before the fardlu prayer begins in the musholla or mosque are oral literature that contains the message of da'wah. Because praise has the same characteristics as oral literature, namely its spread by word of mouth, describes the cultural characteristics of the community, it is not known who the author is, consists of various versions, the language used is everyday spoken language, not concerned with facts and truth, usefulness (function) in the joint activities of a society. Praise also has its own logic that is not in accordance with logic in general, and is innocent and innocent. The praises recited at the Al-Ukhuwah Mosque are part of the Islamic da'wah. The function and usefulness of the praises have messages that provide exemplary lessons, for example there are several da'wah messages, namely da'wah messages about the introduction of the mandatory nature of Allah, about the love of the Apostle, about the antidote to the heart, about the command to pray, and so on.